A eficácia da lei de responsabilidade fiscal sobre os gastos com pessoal: um estudo sobre os gastos com pessoal do poder legislativo em alguns municípios da região metropolitana de Campinas - Berloffa, Marcelo Viaro (2010)
This research studied the effectiveness of the Fiscal Responsibility Law Lei de Responsabilidade Fiscal LRF on the control of personnel expenditures of the Legislative Branch in small municipalities (up to 38.000 inhabitants) in the Campinas metropolitan area, analyzing the evolution of personnel expenditures compared with the other expenditures in order to make personnel expenditures fit the limits established by the Fiscal Responsibility Law FRL. As an initial contextualization, it was carried out a literary revision on the history of public accounting in Brazil, of the Fiscal Responsibility Law, and of personnel expenditures. The analysis assumed the hypothesis of the occurrence of high or increasing expenditures with other public budget rubrics as a way of making personnel expenditures fit the limits established in the article 20, III, of the FRL. It was determined the period 1998 through 2008 to reach this objective. It was analyzed the expenditures before the implementation of the FRL (2000) for subsequent comparison with the behavior of the expenditures after the implementation of the FRL. It was possible to conclude that the personnel expenditures of the Legislative Branch does not have high growth, remaining, on average, at the levels of inflation over the period. However, it could be established that the Legislative Branch of the researched municipalities raised their investments in other rubrics such as consumption supplies, tickets and spending on locomotion, outsourcing, constructions and facilities, equipments and permanent materials